Humanity in times of war? The evacuation of French and Belgian children to Switzerland, 1940 – 1945 - Sambells, Chelsea Ivy Meaghan (The University of Edinburgh, 2016)
This study investigates the evacuation of 60,000 French and Belgian children to Switzerland between 1940 and 1945. This humanitarian action was initially implemented by a coalition of Swiss charities but because of its growing popularity and increasing scope, the Swiss Red Cross joined the efforts in 1942. Despite the devastation, food scarcities and logistical limitations of the Second World War, these children were successfully fed, clothed and housed in Swiss households for three-month periods before they returned home. Given the massive diplomatic and material challenges, it is surprising that such a large transnational evacuation for vulnerable, foreign children was generally effective. By evaluating both how these evacuations were conducted and why participating governments sought to support or prohibit their implementation, this thesis reveals new information that challenges the standard narratives of the wartime actions of the Allies, Nazi Germany and Switzerland. Britain and America’s role in the evacuation does not support their reputation as righteous victors, but as bickering governments strategizing to strengthen their post-war political position in Europe. Nazi Germany’s authorization of the evacuation deepens our knowledge by demonstrating how “humanitarian” operations were circuitously manipulated as a way to increase Nazi control. The noteworthy hospitality of Swiss citizens significantly diverged from the strict immigration policies imposed by their government, a finding which both challenges and reinforces the controversy surrounding Switzerland’s prohibitive, internationally-condemned refugee policies. Overall, this thesis recasts each participant in a new light by questioning the motivations of governments at war, the value of children in war, and the logistics of wartime humanitarian operations.
Keywords: children; war; history; transnational; humanitarianism; Switzerland; evacuation